SaveWise: The design of a financial education program in The Netherlands. (August 2019) - Amagir, Aisa; Groot, Wim; Maassen van den Brink, Henriëtte; Wilschut, Arie
Using a framework for educational design research, this article reports and evaluates the (process of the) design of a financial education program. The program is designed for high school students in the prevocational track in the Netherlands. The aim of the program is to improve students' financial knowledge, attitudes, self-efficacy, and (savings) behavior. The main outcome of this study is the identification of design principles that can be used by others for the design of financial education programs: setting a personal savings goal, commitment with and reflection on this goal, discussing money issues with peers and family, hands-on activities with autonomy, and explicit instruction through animated video clips. The results show that our program, called "SaveWise, " improves high school students' financial knowledge and skills, financial awareness, attitudes towards money, self-efficacy, and financial behavior.